Regional employment In Portugal: differences and cyclical synchronisation - Alves, Mariana (2017)
This paper analyses the specificities of employment in Portuguese regions at a disaggregated level of NUTS III, comparing the differences of several indicators between the last two censuses. It also examines the synchronisation of regional employment cycles over the 2000-2014 period, using the information provided for the new nomenclature of NUTS. The comparison of several employment’s characteristics (total and by sex, age group, sector of activity and main occupation) across the 7 regions and 25 sub-regions allowed us to conclude that Portugal is marked by substantial regional specificities. The analysis of the evolution of employment ‘cycles highlight the substantial reduction in the employment rate since the beginning of the 2000s, with particular intensity in the period of the recent crisis, and considerable differences across regions and at the intraregional level. The results from the synchronisation reveal a great heterogeneity in the degree of correlation between the sub- national cycles and the national cycle. Additionally, they suggest that, in general, the cyclical pattern of the sub-regions is more closely related to the regions that they belong to than that of the Portuguese cycle. The paper concludes that this heterogeneity should be addressed in the context of policy making, by means to construct appropriate responses to counteract the regional differences.